Spinning Straw into Milk: Can an All- Byproduct Diet Support Milk Production? - M. Hulett; C. Ylioja; T. Wickersham; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2015)
Ruminants are able to consume feeds that are unsuitable for humans and monogastric animals, and thus contribute to increased efficiency of our food systems. This study evaluated the performance of dairy cows consuming a diet comprised almost entirely of byproduct feeds, compared with cows consuming a typical lactation diet. The hypothesis was that the byproduct diet could support 80 lb/day of milk production. Although milk production and crude feed efficiency decreased compared to the typical diet, feed efficiency expressed as human-edible output per human-edible input increased for the byproduct diet. This study highlights the unique and important role played by ruminant agriculture in the quest for improved sustainability of our food systems.
Keywords: nutrition; lactation; sustainability; byproduct